Vitamin D: Relations with Sleep and Bone Mineral Density. Insights from the Tromsø Study and randomized controlled trials - Larsen, Anette Uhlving (UiT The Arctic University of Norway, 2022)
In this thesis, the relationship between vitamin D and health-related outcomes has been investigated. More than 21,000 individuals participated in the Tromsø Study 2015-16. The participants donated blood samples and filled in questionnaires regarding their health status, including questions about their sleep health. Using these data, the association between vitamin D and sleep duration, daytime sleepiness, and insomnia (sleeplessness) were explored. In women, a positive association was found between vitamin D and sleep duration, while the prevalence of insomnia was lower in women with a normal vitamin D level compared to women with higher vitamin D levels. To further explore this relationship, the effect of vitamin D supplementation on sleep duration, daytime sleepiness, and prevalence of insomnia was explored. A sleep questionnaire was implemented as part of an ongoing intervention study, originally designed to evaluate the effect of vitamin D supplementation for the prevention of cardiovascular disease. In total, 189 participants with low vitamin D levels at baseline filled in the sleep questionnaire. After four months of treatment, there were no differences in sleep duration, daytime sleepiness, or prevalence of insomnia between the group taking vitamin D versus placebo, neither when stratified by sex, nor by vitamin D level or sleep status at baseline. It was further investigated in another intervention study whether vitamin D supplementation without additional calcium could have a positive effect on bone mineral density, as a preventive measure against deteriorated bone health. In this intervention study, originally designed to evaluate vitamin D for the prevention of type 2 diabetes, it was found that vitamin D supplementation alone had a positive effect on bone mineral density in men, and that the effect appeared to vary according to measurement site. I denne doktorgraden har sammenhengen mellom vitamin D og helserelaterte endepunkter blitt undersøkt. I 2015-16 deltok mer enn 21,000 personer i ...